ANALISIS KESULITAN PENULISAN HANZI PADA SISWA KELAS VI SD ZION GKKA-UP MAKASSAR DALAM PEMBELAJARAN BAHASA MANDARIN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify and analyze the difficulties experienced by students in writing Hanzi. The method used is a quantitative descriptive approach, with data collected through writing tests and questionnaires distributed to students of SD Zion GKKA-UP Makassar who are learning Mandarin.The results of the study reveal that students still face various challenges, with stroke order being the most dominant difficulty (100%). This is followed by difficulties in maintaining proportion and character structure (86.7%), neatness of writing (60.0%), and distinguishing characters with similar forms (40.0%).The factors influencing these difficulties include a lack of practice time and variation in teaching methods (100%), unfamiliarity with strict writing rules (66.7%), as well as students’ perceptions of the potential of digital media in increasing learning motivation (86.7%).